HUBUNGAN FASILITAS MEETING ROOM DENGAN KEPUTUSAN PEMBELIAN JASA BANQUET OLEH KONSUMEN DI HOTEL GRAND INNA MUARA PADANG - A, Lathif Arafat; Silfeni, Silfeni; Abrian, Youmil (Journal of Home Economics and Tourism, 2015)
This purpose of research is to analyze the relation between meeting roomfacilities with buying decision by costumers in the Grand Inna Muara Padang. Thetype is the correlation. Populations in this study are goverment departments andprivate department which has been used banquet service in the Grand Inna MuaraHotel Padang period January-August 2014 about 135 departments which thesample about 78 departments which has been compare to 3 categories with takingsample sampling proportionate strafied random. Data collection based to likertscale. The result showed that: 1)Meeting Room Facilities are in the good category(56%); 2)Buying Decision are in the good category (42%); 3)Result correlationPerason Product Moment test with significance of 5%, showed that rhitung 0,457 inthe rtabel 0,25-0,5, although Ha received.Keyword: Meeting Room Facilities, Buying Decision of Banquet Service